Design thinking basics : an introduction to the DTMethod - Czarny, Rafał; Chrząszcz, Agnieszka; Eromin, Michał (TSO (The Stationery Office), 2023)
Design thinking is an approach to designing new products, processes and services (‘solutions’). Solutions are designed and delivered using a variety of models, tools and methods, depending on the preferences of a given organization and the challenges it faces. Design thinking is not a single methodology, but a way of working that is open to various methods of operation, depending on the needs of the team and the requirements of stakeholders.